2004
DOI: 10.1556/avet.52.2004.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and pathology of Sinergasilus lieni (Copepoda: Ergasilidae), a parasite of the silver carp and bighead, in Hungarian ponds

Abstract: Sinergasilus lieni Yin, 1949, a well-known and pathogenic parasitic copepod in China and Russia, has been detected in Hungarian carp farms for the first time. The parasite infected the third-year generation of silver carp (Hypophthalmichthys molitrix) and bighead (Aristichthys nobilis). The gills of the infected fish specimens showed severe pathological changes. At the attachment sites of female copepods clubbing and fusing of the gill filaments were observed and in some parts of the pale or whitish hemibranch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…Dezfuli, Squerzanti, Fabbri, Castaldelli, and Giari () and Dezfuli, Giari, Lui, Lorenzoni, and Noga () besides hypertrophy of epithelioid cells observed haemorrhage, increase of rodlet cells, mast cells and mucous cells adjacent to the attachment site of copepods. Similar changes were caused by Sinergasilus lieni Yin, 1949 on silver carp in Hungary when besides the above mention signs, clubbing, fusion of neighbouring filaments were recorded (Molnár & Székely, ). In the present study, Lamproglena infections exhibited pathogenic changes on the tip of gill filaments.…”
Section: Discussionsupporting
confidence: 55%
“…Dezfuli, Squerzanti, Fabbri, Castaldelli, and Giari () and Dezfuli, Giari, Lui, Lorenzoni, and Noga () besides hypertrophy of epithelioid cells observed haemorrhage, increase of rodlet cells, mast cells and mucous cells adjacent to the attachment site of copepods. Similar changes were caused by Sinergasilus lieni Yin, 1949 on silver carp in Hungary when besides the above mention signs, clubbing, fusion of neighbouring filaments were recorded (Molnár & Székely, ). In the present study, Lamproglena infections exhibited pathogenic changes on the tip of gill filaments.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have reported that the mode of attachment and feeding activity of parasitic copepods were the main reasons of damage to the gills [6,7]. Indeed, it was mentioned that ergasilid copepod infections can reduce gill function, resulting in decreased growth rate due to impaired respiration, morbidity and often substantial mortality in brackish water fish [11,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, feeding activity and mode of attachment of these copepods are the main reason for host damage and has been addressed in previous studies [6,7]. According to Johnson et al (2004) [4], outbreaks of disease due to ergasilids are a major source of copepod-induced mortality in brackish and freshwater fish culture of several countries, including Israel [8], Taiwan [9], Japan [10], China [11], the USA [12], South Africa [13] and Hungary [14]. In Italy, in our study area, in summer 2006, the copepod, Ergasilus sp.…”
Section: Introductionmentioning
confidence: 99%
“…While Diplectanum aequans (Wagener) destroys the secondary lamellae of European sea bass Dicentrarchus labrax (L.) gills, infections by Neoheterobothrium hirame Ogawa on gills of Japanese flounder Paralichthys olivaceus (Temminck & Schlegel) only causes a pathological change when attached to the buccal wall leading to necrosis of the dermis and underlying tissue (Ogawa, 2002; Dezfuli et al , 2007 b ). Eosinophilic granular cells are reduced in number in D. aequans infections but elevated in Ergasilus sieboldi Nordmann infections on the gills of the common bream Abramis brama (L.) and infections by Sinergasilus polycolpus (= lieni ) (Markewitsch) on gills of silver carp Hypophthalmichthys molitrix (Valenciennes) and bighead carp Aristichthys nobilis (Richardson) (Cakic et al , 2004; Molnár & Székely, 2004; Williams, 2007) [Fig. 1(h)].…”
Section: Pathogenicity At the Individual Level According To Parasite mentioning
confidence: 99%